Optimizing the Ratio Concept Learning through Game Wordwall in 4th Grade Elementary School - Irhas, Irhas; Hidayat, Irfan; Muhammad, Muhammad; Lutfi, Muhammad; Hadi, Heri Sopian (Lembaga Yasin AlSys, 2025)
This study aimed to evaluate the effectiveness of using Wordwall games to enhance fourth-grade elementary school students' understanding of ratio concepts. A one-group pretest-posttest design was implemented involving 19 participants. Data were gathered through pretest and posttest assessments administered before and after the instructional intervention utilizing Wordwall games. The results of the paired samples t-test revealed a statistically significant improvement in students' performance, with pretest scores (M = 42.63, SD = 11.349) substantially lower than posttest scores (M = 80.79, SD = 9.319), t(18) = -29.806, p < .001. Additionally, Pearson correlation analysis indicated a strong and significant positive relationship between pretest and posttest scores (r = 0.872, p < .001), suggesting consistency in learning gains. These findings demonstrate that integrating gamified learning tools such as Wordwall games can effectively support students’ comprehension of mathematical concepts, particularly ratios. The study underscores the pedagogical value of gamification in elementary mathematics education, offering both cognitive and motivational benefits that contribute to improved learning outcomes.